Analisis Implemmentasi Pelayanan Penggunaan Aplikasi Pengaduan Pelanggan Berbasis Aplikasi Pelayanan Keluhan Terpadu (APKT) Untuk Meningkatkan Kepercayaan Masyarakat Pada PT.PLN (Persero) - SITI NURJANAH; Tuswoyo Tuswoyo (Institut Ilmu Sosial dan Manajemen STIAMI, 2022)
This research is motivated by the high number of customer complaints. The purpose of this research is to identify the “Implementation of Integrated Complaint Service Application or Aplikasi Pelayanan Keluhan Terpadu (APKT)-Based Customer Complaint Application Service in Improving Public Trust in PT.PLN (Persero). This research uses qualitative descriptive method to describe and explain in detail the existing phenomena by using interview as its supporting instrument. The result of this research shows that the implementation of the service is not yet optimal. The obstacle includes human error where officers do not have sufficient knowledge about cash management system application. The efforts made to overcome the obstacle includes socialization to officers in order to better operate the system.